Colton 911: detective on call - Black, Regan (Harlequin romantic suspense, 2020)
"Detective Emmanuel Iglesias does his duty at all costs, even if that means going up against Pippa Colton. The stubborn attorney insists her client is innocent, but Emmanuel knows that his case is rock-solid. That is, until Pippa becomes a target herself. Is the real killer still at large? As their mutual distrust turns into an undeniable attraction, the murderer becomes bolder--and more menacing..." --Amazon.